Changes in molybdenum bioaccessibility in four spiked soils with respect to soil pH and organic matter. (15th May 2023) - Shi, Yangxiaoxiao; Yu, Yunjiang; Xiang, Mingdeng; Cui, Peixin; Cui, Jiaqi; Zhang, Feng; Jiang, Jun; Xu, Renkou
Abstract: Investigation of the inherent relationship between soil physicochemical properties and pollutant's bioaccessibility (BAc) by analyzing different soil types may produce erroneous results or bias, owing to the complexity of natural soil characteristics. However, use of single factor analysis (e.g., soil pH, organic matter) facilitates evaluation of the transition. In this study, the inherent relationship between soil properties and the BAc of molybdenum (Mo) was evaluated in two typical variable-charge soils (Ferralosol and Ferrosol) and constant-charge soils (Alfisol and Inceptisol) spiked with Mo after adjusting their pH and organic carbon content. The Unified Bioaccessibility Research Group of Europe (BARGE) Method (UBM) was applied to evaluate the BAc of Mo in the gastric and intestinal phase (GP and IP, respectively). Isothermal adsorption experiment, Tessier sequential extraction, and field emission scanning electron microscope-energy dispersive spectroscopy (FESEM-EDS) analysis were conducted on these spiked soils. The results indicated that the BAc of Mo in IP (27.42–80.41%) was significantly higher than that in GP (2.52–28.53%). A significantly lower level of BAc of Mo was found in the variable-charge soils, when compared with that in the constant-charge soils. Furthermore, significant negative correlations were identified between the BAc and adsorption of Mo, which decreased with soil pH. These negative correlations can be attributed to the increase in soil negative charge density and enhancement of Mo desorption by hydroxyl, which reinforce the repulsion between Mo and soil particles with increasing soil pH; this was further confirmed by the decrease in Mo adsorption with Alfisol pH. The Mo fractions and FESEM-EDS patterns confirmed that the BAc of Mo in GP was negatively correlated with soil organic carbon (SOC) content, possibly owing to an increase in Mo retention by SOC. These findings indicated that the health risk of Mo contamination in low pH and SOC-rich variable-charge soil is relatively low, thus providing references for rationalizing risk assessment and remediating Mo-polluted soil. Graphical abstract: Image 1 Highlights: Molybdenum bioaccessibility is mainly related to soil pH, free iron and aluminum oxides and organic carbon. Molybdenum bioaccessibility in gastric phase is significantly lower than that in intestinal phase. Free iron and aluminum, and organic carbon achieve short- and long-term molybdenum inactivation, respectively.